A meta-analysis: the effect of the means-ends analysis model on student learning outcomes - Sahabudin, Ahmad; Agustina, Dwi; Zayana, Husrawati; Ibrohim, Malik (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
ABSTRACTThis study aims to determine the effect of the model Means-Ends Analysis on student learning outcomes (SD, SMP, SMA) and subjects (Mathematics, Social Sciences, Science). The data from this research is collected through indexing databases such as Google Scholar,Sintaand the Garuda Portal. From search results with keywords means-ends analysisand learning outcomes from 2013 to 2020 found 45 articles that met the research requirements. The results of the search for 45 data will be filtered to look for the values of N, Fcount, tcount, and rcount. The research method uses Meta-Analysis with a learning model menas-ends analysis on student learning outcomes. The results showed thatobtained summary effect value of 0.66 or 66%, including the strong category in influencing the improvement of student learning outcomes. The results of the moderator variable data analysis show that at the SD level it has an influence of 81% which indicates that the influence is very strong. Meanwhile, at the junior and senior high school levels, they have the same strong influence, namely, 64% and 66%. This shows that the Means-Ends Analysis method is suitable for all levels. Then for the results of the classification data analysis subjects obtained the strongest influence, namely social studies subjects with an effect of 75%. Meanwhile, mathematics has a strong effect of 68% and science has a moderate effect of 53%.